me Pengaruh Layanan Bimbingan Kelompok dengan Teknik Modeling Untuk Meningkatkan Kedisiplinan Siswa SMP Negeri 22 Kota Bengkulu: Abstark, Pendahuluan, Metode Penelitian, Hasil Penelitian, Pembahasan, Kesimpulan, Daftar Pustaka - Ganda Boangmanalu; Hadiwinarto; Arsyadani Mishbahuddin (UNIVERSITAS BENGKULU, 2023)
This study aims to describe the influence of modeling engineering group guidance services to improve the disciplinary character of SMP Negeri 22 Bengkulu City. This research uses an experimental method with a one group pre-test and post-test pattern. The population of this study was 53 students with a sample of 10 students determined using random sampling techniques. The data collection technique uses a student discipline questionnaire instrument with a Likert scale model. Based on the results of the hypothesis test analysis, tcount = -7.588. Next, the t table was consulted with a significance level of 5% (0.05), namely 2.308. Shows the value of t count = -7.588> t table = 2.308 Ha is accepted. This means that there is a significant influence of modeling engineering group guidance services on student discipline. Keywords: group guidance, modeling technique, student’s discipline